SI BITA - DESIGN OF A THESIS GUIDANCE INFORMATION SYSTEM USING THE SCRUM METHOD FOR OPTIMAL EFFICIENCY AND RESPONSIVENESS - Pernando, Yonky; Syafrinal, Ilwan; KH, Musliadi (STMIK Royal, 2024)
Abstract: This research aims to design a system that can assist the final assignment development process by focusing on resolving frequently encountered obstacles, such as clarity of research title status, guidance process, and research schedule. The development method used is the Scrum method approach with a small scale and team. During the development process, an analysis of each sprint is carried out from preparation to the development process. The results of development using the Scrum method show that each feature was completed within 8 hours per day, with each sprint completed in a week. The total time required to complete all sprints designed on the BITA Information System is 128 hours. The application of the Scrum method provides results that enable rapid identification of changes during the development process, as well as optimizing the process of submitting and validating titles, determining supervisors, evaluating guidance, and scheduling exams. Thus, this research provides an effective solution in increasing the efficiency and effectiveness of the final assignment coaching process for students in completing their studies. Keywords: information system; optimal efficiency; scrum method; SI BITA; thesis guidance. Abstrak: Penelitian ini bertujuan untuk merancang sistem yang dapat membantu proses pembinaan tugas akhir dengan fokus pada penyelesaian kendala yang sering dihadapi, seperti kejelasan status judul penelitian, proses bimbingan, dan jadwal penelitian. Metode pengembangan yang digunakan adalah pendekatan metode Scrum dengan skala dan tim kecil. Selama proses pengembangan, dilakukan analisis terhadap setiap sprint yang dihasilkan dari persiapan hingga proses pengembangan. Hasil pengembangan menggunakan metode Scrum menunjukkan bahwa setiap fitur diselesaikan dalam jangka waktu 8 jam per hari, dengan setiap sprint selesai dalam seminggu. Total waktu yang dibutuhkan untuk menyelesaikan semua sprint yang dirancang pada Sistem Informasi BITA adalah 128 jam. Penerapan metode Scrum memberikan hasil yang memungkinkan identifikasi cepat terhadap perubahan selama proses pengembangan, serta mengoptimalkan proses pengajuan dan validasi judul, penentuan pembimbing, evaluasi bimbingan, dan penjadwalan ujian. Dengan demikian, penelitian ini menyediakan solusi yang efektif dalam meningkatkan efisiensi dan efektivitas proses pembinaan tugas akhir bagi mahasiswa dalam menyelesaikan studi mereka. Kata kunci: sistem informasi; efisiensi optimal; metode scrum; SI BITA; bimbingan skripsi